Small suprapubic incision facilitates consent in perinatal and pediatric necropsies - Romero, Nery (2016)
Objective. To report a new approach for perinatal and pediatric necropsy that allows parental consent. Methods. Experience with necropsies in 20 stillborn, 15 neonates and 8 infants is presented with this new approach; the parents had refused the use of the standard body incision. Through a small transversal about 10 cm incision in the suprapubic region, manual evaluation of the abdominal and pelvic cavities was performed, and then the viscera were obtained by either the Letulle`s technique (a single block) or the Virchow´s technique (organ by organ). The incision is closed by subdermic suture. Conclusions. This technique is well accepted by the parents because the skin surface and the body as a whole appear little disturbed.